A Study of Students’ Mathematical Concept Understanding Ability: Learning Anxiety and Independence in Learning Mathematics (Journal Evaluation in Education (JEE), 2025)
Purpose of the Study: This study aims to explore fourth-grade students’ understanding of mathematical concepts by examining two psychological and behavioral variables: mathematics anxiety and learning independence. Specifically, the study investigates how these two factors influence students’ abilities to comprehend and apply mathematical concepts in classroom learning. Addressing this issue is essential, as early mathematical understanding serves as a foundation for more complex problem-solving in later education.Methodology: This research employs a qualitative case study approach, with data collected through classroom observations, structured interviews with students and teachers, and analysis of related documents, including student worksheets, math test scores, and teacher reflections. The study utilizes a customized analytical framework based on a modified version of Bloom’s Taxonomy, allowing for a detailed exploration of cognitive understanding, emotional responses, and metacognitive strategies in relation to mathematical learning.Main Findings: Findings indicate that many fourth-grade students experience moderate to high levels of math anxiety, often rooted in negative prior experiences. This anxiety correlates with lower conceptual understanding and reduced classroom performance. Conversely, students who demonstrate high learning independence characterized by initiative, persistence, and self-regulation tend to show greater comprehension and confidence in learning mathematics, even in the face of challenging tasks.Novelty/Originality of this study: The novelty of this study lies in its integrative framework that connects emotional (anxiety), behavioral (independence), and cognitive (conceptual understanding) domains in elementary mathematics education. It also introduces a structured interview instrument designed specifically to uncover students’ internal learning experiences, providing deeper insight into early mathematical development.
Keywords: Mathematical Concept; Learning Anxiety; Learning Independent; Students